2020
DOI: 10.1186/s13075-020-02181-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation of NF-κB by TNFAIP3 (A20) reduction and UBE2L3 (UBCH7) augment that synergistically elevate lupus risk

Abstract: Background: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory rheumatic disease. SLE susceptibility is affected by multiple genetic elements, environmental factors, and their interactions. We aimed in this study to statistically and functionally characterize a gene-gene interaction (epistasis) recently documented to affect SLE risk. Methods: Two single-nucleotide polymorphisms, rs2230926 in TNFAIP3 (A20) gene and rs131654 in UBE2L3 (UBCH7) gene, were genotyped in all 3525 Korean participants, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…NF-κB signaling pathway may be activated or inactivated by different factors or stimulation signals, such as tumor necrosis factor-A, IL-6, Caspase-3, c-Jun N-terminal kinase and ROS 37 . On the contrary, activation of NF-κB can induce the expression of many proinflammatory genes, including COX-2, TNF-α, IL-6 and iNOS 38 . Previous studies have shown that GM can induce severe inflammatory reactions, including activation of NF-κB and iNOS, and the production of TNF-α 39 .…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling pathway may be activated or inactivated by different factors or stimulation signals, such as tumor necrosis factor-A, IL-6, Caspase-3, c-Jun N-terminal kinase and ROS 37 . On the contrary, activation of NF-κB can induce the expression of many proinflammatory genes, including COX-2, TNF-α, IL-6 and iNOS 38 . Previous studies have shown that GM can induce severe inflammatory reactions, including activation of NF-κB and iNOS, and the production of TNF-α 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It is both deubiquitinating and is an ubiquitin ligase. The vital involvement of this protein in regulating inflammatory signal transduction [15,16] to negatively regulate the NF-κB pathway via feedback and inhibit NF-κB pathway activation via several inflammatory signals has been shown [17][18][19][20]. It can inhibit the transcription of downstream inflammatory factors and has a strong anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Latest investigations suggest that another predominantly in lymphocytes expressed ubiquitin-carrier enzyme E2L3 ( UBE2L3 ) is a risk gene that influences autoimmunity by modulating UBCH7 expression. 50 , 51 Experimental studies in mice showed that the MCPIP1 protein negatively regulates c-Jun N-terminal kinase (JNK) and NF-κB activity by removing ubiquitin moieties from TRAF proteins, which determines autoantibodies in SLE. 52 , 53 Furthermore, the interleukin-1 receptor (IL-1R) associated kinase (IRAK) family, which plays a crucial role in the protective response to pathogens and inflammatory processes, is involved in the susceptibility to SLE.…”
Section: Effect Of Monogenic and Polygenic Defects On Autoimmunitymentioning
confidence: 99%